Compilation of Islamic Laws Regarding Marrying Pregnant Women: The Case of Biau Regency, Central Sulawesi - Isman, Isman; Thahir, Lukman S.; Adam, Adam (State Islamic University Datokarama Palu, 2023)
Previously, in Indonesia, there was no written law regarding the settlement of premarital pregnancy married. Society usually uses a solution by carrying out a marriage between the pregnant woman and the man who impregnated her without waiting for the birth of the child she is carrying. This method aims to cover up the disgrace so that it is not known to the wider public. As long as the perpetrators of adultery and their families are able to keep this secret, then the adulterers and their children will be safe from society's response. This used qualitative method to study compilation of Islamic laws regarding marrying pregnant women in Biau district, Buol regency. The results of this study show that premarital pregnancy married can be recorded and made a marriage certificate during the marriage procession at the religious courts, even though the marriage ceremony was not carried out at that time or was carried out at that time. When a prospective bride is pregnant and then immediately married, the shame of both the prospective bride and her family should be covered. This is also based on the hadith narrated by Muslims, which reads: